Perancangan Strategis Blueprint Sistem Informasi menggunakan Metode Enterprise Architecture Planning Studi Kasus Universitas Kartamulia Purwakarta - Divi Adiffia Freza Alana; Salim, Asep Yusapra; Putri, Rizqy Amalia; Mardiman; Basysyar, Fadhil Muhammad (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2025)
The increasing need for integrated information systems in higher education requires a strategic and structured architectural plan. Universitas Kartamulia Purwakarta faces challenges from fragmented systems among departments and the absence of a long-term roadmap for information technology development. This study aims to design a strategic information system blueprint using the Enterprise Architecture Planning (EAP) method to support the university’s core processes. A descriptive qualitative approach with a case study method was applied. Data were collected through interviews, observations, and document analysis. The EAP stages include Planning Initiation, Business Modeling, Current System Analysis, Data Architecture, Applications Architecture, Technology Architecture, and Implementation Planning. The results produce an integrated architecture blueprint covering key domains such as student admissions, academic processes, research, and student services. This blueprint provides a strategic foundation for aligning information systems with institutional goals and improving operational effectiveness. The proposed design strengthens the university’s digital transformation and supports the realization of an integrated, efficient, and competitive smart campus.